On the exponential growth of solutions to non-linear hyperbolic equations - H. Chi; H. Poorkarimi; J. Wiener; S. M. Shah (International Journal of Mathematics and Mathematical Sciences)
Existence-uniqueness theorems are proved for continuous solutions of some classes of non-linear hyperbolic equations in bounded and unbounded regions. In case of unbounded region, certain conditions ensure that the solution cannot grow to infinity faster than exponentially.